Survival and clinical outcomes of children starting renal replacement therapy in the neonatal period - Stralen, Karlijn J. van; Schaefer, Franz (Kidney international, 2014)
End-stage renal disease requiring renal replacement therapy (RRT) during the neonatal period is a very rare condition, and little information is available regarding long-term RRT and outcomes. To gain more information, we performed a collaborative study on patient characteristics and treatment outcomes in children who started RRT as neonates during their first month of life between 2000 and 2011 who were prospectively registered in the ESPN/ERA-EDTA, the IPPN (since 2007), the Japanese registry, or the Australian and New Zealand Dialysis and Transplant (ANZDATA) registry. During the first month of life, 264 patients from 32 countries started RRT and were followed for a median of 29 months (interquartile range 11-60 months). Most neonates (242) started on peritoneal dialysis, 21 started on hemodialysis, and 1 patient with a transplant. The most important causes of renal failure were congenital anomalies of the kidney and urinary tract in 141, cystic kidneys in 35, and cortical necrosis in 30. Within 2 years after the start of RRT, 69 children changed dialysis modality and 53 received a renal transplant. After a median of 7 months, 45 children had died, mainly because of infection, resulting in an estimated 2-year survival of 81%, and 5-year survival of 76%. Growth retardation (63%), anemia (55%), and hypertension (57%) were still major problems after 2 years. Thus, relatively good medium-term patient survival may be achieved with RRT started during the neonatal period, but specific therapeutic challenges continue to exist in this age group.
Gesehen am 21.08.2020
Der Name "Kariljn J. van Stralen" ist in der Verfasserangabe falsch geschrieben